(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to analyze the phenomenon of interference linguistically within the framework of different language levels. Methods of linguistic analysis, comparison and contrast were used in the research. According to the results of the research, the closer the languages are to each other, the higher the probability of positive interference, and the more dissimilar languages, the higher the probability of negative interference. It was concluded that interference is a process that occurs in the interaction of languages and is manifested at all levels of language.